Brushed in light : calligraphy in East Asian cinema - Nornes, Markus (University of Michigan Press, 2021)
"Brushed in Light examines how the brushed word appears in films and in film cultures of Korea, Japan, Taiwan, Hong Kong, and PRC cinemas. This includes silent era intertitles, subtitles, title frames, letters, graffiti, end titles, and props. Professor Nornes also looks at the role calligraphy plays in film culture at large, from gifts to correspondence to advertising. The book begins with a historical dimension, tracking how calligraphy is initially used in early cinema and how it is continually rearticulated by transforming conventions and the integration of new technologies. It then considers how cinematic writing presents the peculiarities of calligraphy as resources for innovative screenwriters and filmmakers. These chapters ask how calligraphy creates new meaning in cinema, as well as providing a demonstration of how this all works in a single film. The last part of the book moves to other regions of theory, particularly questions surrounding the cinematization of the handwritten word"--